Integrated digital advisory services to smallholder farmers: the case of wheat value chain in Ethiopia - Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Accelerating Research, Innovation, Technology Transfer for African Adaptation to Climate Change. High-level dialogue: From Science to Action Rabat, Morocco. October 15th, 2021,